Entamoeba marina n. sp.; a New Species of Entamoeba Isolated from Tidal Flat Sediment of Iriomote Island, Okinawa, Japan. (6th November 2015) - Shiratori, Takashi; Ishida, Ken‐ichiro
Abstract: The genus Entamoeba includes anaerobic lobose amoebae, most of which are parasites of various vertebrates and invertebrates. We report a new Entamoeba species, E . marina n. sp. that was isolated from a sample of tidal flat sediment collected at Iriomote Island, Okinawa, Japan. Trophozoites of E .  marina were 12.8–32.1 μm in length and 6.8–15.9 μm in width, whereas the cysts were 8.9–15.8 μm in diam. and contained four nuclei. The E . marina cells contained a rounded nucleus with a small centric karyosome and uniformly arranged peripheral chromatin. Although E . marina is morphologically indistinguishable from other tetranucleated cyst‐forming Entamoeba species, E . marina can be distinguished from them based on the combination of molecular phylogenetic analyses using SSU rDNA gene and the difference of collection sites. Therefore, we propose E . marina as a new species of the genus Entamoeba .